"Keeping up with the Joneses?" How Perceived SES Moderates the Relationship between Economic Problems and Instrumental Crime. Issue 10 (2nd October 2016) - Dennison, Christopher R.
ABSTRACT: The present study examined the moderating effects of perceived socioeconomic status (SES) on the relationship between economic problems and instrumental crime. Using data from the National Longitudinal Study of Adolescent to Adult Health ( N = 14, 754), results suggested that the effect of economic problems on crime exhibited an inverted-U-shaped curve. The effect was moderated by perceived SES such that those with the highest levels of perception reported the highest involvement in crime when experiencing a few economic problems. Conversely, high perceived SES among those experiencing excessive economic problems acted as a protective factor in criminal involvement.